تحليل الأخطاء النحوية في قراءة نص مادة القراءة - Majid, Muhamad Nurkolis; Sanah, Siti (Al-Muyassar: Journal of Arabic Education, 2024)
The ability of an individual to read Arabic texts heavily depends on their understanding of Arabic grammar. Students' comprehension of grammatical rules significantly affects the accuracy of reading because any errors in reading Arabic texts can alter their meanings. The reading proficiency of students at the linguistic institute, coupled with their diverse educational backgrounds, often leads to grammatical errors in reading Arabic texts. Therefore, this research aims to identify the grammatical errors in reading Arabic texts and to discover the factors that cause students to make these errors. By understanding these factors, educators can find solutions to address and resolve these issues. The research methodology employed in this study is descriptive with a qualitative approach. Data collection methods include observations and direct interviews with several students from the linguistic institute and their reading instructor, to gather the necessary information for this research.Keywords: Analisis Kesalahan, Nahwu, Qiraah مستخلص البحثتعتمد قدرة الفرد على قراءة النصوص العربية بشكل كبير على فهمه لقواعد اللغة العربية. يؤثر فهم الطلاب للقواعد النحوية بشكل كبير على دقة القراءة لأن أي أخطاء في قراءة النصوص العربية يمكن أن تغير معانيها. غالبا ما تؤدي كفاءة القراءة لدى الطلاب في المعهد اللغوي، إلى جانب خلفياتهم التعليمية المتنوعة، إلى أخطاء نحوية في قراءة النصوص العربية. لذلك يهدف هذا البحث إلى التعرف على الأخطاء النحوية في قراءة النصوص العربية واكتشاف العوامل التي تسبب وقوع الطلاب في هذه الأخطاء. من خلال فهم هذه العوامل ، يمكن للمعلمين إيجاد حلول لمعالجة هذه المشكلات وحلها. منهجية البحث المستخدمة في هذه الدراسة وصفية ذات منهج نوعي. وتشمل طرق جمع البيانات الملاحظات والمقابلات المباشرة مع العديد من طلاب المعهد اللغوي ومعلم القراءة الخاص بهم، لجمع المعلومات اللازمة لهذا البحث.الكلمات المفتاحية: تحليل الأخطاء, نهوو, قراءه.